The Flash. The complete fifth season [videorecording (DVD)] - Cavanagh, Thomas, 1963- (Warner Bros. Home Entertainment, 2019)
Shortly after defeating the Thinker, Barry Allen/the Flash and his wife, Iris, were stunned by the arrival of their already grown, speedster daughter from the future, Nora. However, acclimating to their lives as parents won't be the only challenge they face, as season five pits Team Flash against Central City's latest scourge, the DC Super-Villain Cicada.